2006
DOI: 10.1039/b604520k
|View full text |Cite
|
Sign up to set email alerts
|

23Na multiple-quantum MAS NMR of the perovskites NaNbO3and NaTaO3

Abstract: The distorted perovskites NaTaO(3) and NaNbO(3) have been studied using (23)Na multiple-quantum (MQ) MAS NMR. NaTaO(3) was prepared by high temperature solid state synthesis and the NMR spectra are consistent with the expected room temperature structure of the material (space group Pbnm), with a single crystallographic sodium site. Two samples of NaNbO(3) were studied. The first, a commercially available sample which was annealed at 900 degrees C, showed two crystallographic sodium sites, as expected for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
75
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 39 publications
(107 reference statements)
10
75
0
Order By: Relevance
“…Na 0:5 K 0:5 NbO 3 is one of the important lead-free piezoelectric materials with perovskite structure. Studies on various aspects of phase transitions in Na 0:5 K 0:5 NbO 3 have been reported using a variety of experimental techniques, including X-ray absorption fine structure (Shuvaeva et al, 2001), transmission electron spectroscopy (Chen & Feng, 1988), electron paramagnetic resonance (Avogadro et al, 1974), nuclear magnetic resonance (D'Ariano et al, 1982;Ashbrook et al, 2006) and Raman spectroscopy (Mishra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Na 0:5 K 0:5 NbO 3 is one of the important lead-free piezoelectric materials with perovskite structure. Studies on various aspects of phase transitions in Na 0:5 K 0:5 NbO 3 have been reported using a variety of experimental techniques, including X-ray absorption fine structure (Shuvaeva et al, 2001), transmission electron spectroscopy (Chen & Feng, 1988), electron paramagnetic resonance (Avogadro et al, 1974), nuclear magnetic resonance (D'Ariano et al, 1982;Ashbrook et al, 2006) and Raman spectroscopy (Mishra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This method, which uses pseudopotentials and plane wave basis sets to describe the system, [30] has gained popularity recently for the calculation of SSNMR parameters. [13,[31][32][33][34][35][36][37][38] …”
Section: Introductionmentioning
confidence: 99%
“…Since it has been demonstrated that projector augmented wave (PAW) based density functional theory (DFT) calculations yield reasonable values of electric field gradient components in solids26, several combined experimental-theoretical studies of perovskites have been published. There are, for example, DFT-assisted assignments of crystal structures based on electric field gradients for NaNbO 3 272829, PbZr 1- x Ti x O 3 30 or La x Y 1- x ScO 3 31. Besides being a suitable method to assist the interpretation of NMR spectra, DFT calculations are also a well-suited tool to explore the relationship between electric field gradients and structural features in order to reveal general structure-property relations.…”
mentioning
confidence: 99%